Neighbourhood unemployment and other socio-demographic predictors of emergency hospitalisation for infectious intestinal disease in England: A longitudinal ecological study. Issue 5 (November 2020) - Rose, Tanith C.; Adams, Natalie L.; Whitehead, Margaret; Wickham, Sophie; O'Brien, Sarah J.; Hawker, Jeremy; Taylor-Robinson, David C.; Violato, Mara; Barr, Benjamin
Highlights: We examined trends in infectious intestinal disease (IID) hospitalisations in England. Overall IID admission rates for children and older adults declined between 2012 & 2017. Increasing unemployment was associated with increasing IID admission rates. Healthcare access, underlying morbidity and ethnicity were also associated with IID rates. Policies should address inequalities in emergency IID hospitalisations. Summary: Background: Previous studies have observed that infectious intestinal disease (IID) related hospital admissions are higher in more deprived neighbourhoods. These studies have mainly focused on paediatric populations and are cross-sectional in nature. This study examines recent trends in emergency IID admission rates, and uses longitudinal methods to investigate the effects of unemployment (as a time varying measure of neighbourhood deprivation) and other socio-demographic characteristics on IID admissions for adults and children in England. Methods: A longitudinal ecological analysis was performed using Hospital Episode Statistics on emergency hospitalisations for IID, collected over the time period 2012–17 across England. Analysis was conducted at the neighbourhood (Lower-layer Super Output Area) level for three age groups (0–14; 15–64; 65+ years). Mixed-effect Poisson regression models were used to assess the relationship between trends in neighbourhood unemployment and emergency IID admission rates, whilst controlling for measures of primary and secondary care access, underlying morbidity and the ethnic composition of each neighbourhood. Results: From 2012–17, declining trends in emergency IID admission rates were observed for children and older adults overall, while rates increased for some sub-groups in the population. Each 1 percentage point increase in unemployment was associated with a 6.3, 2.4 and 4% increase in the rate of IID admissions per year for children [IRR=1.06, 95%CI 1.06–1.07], adults [IRR=1.02, 95%CI 1.02–1.03] and older adults [IRR=1.04, 95%CI 1.036–1.043], respectively. Increases in poor primary care access, the percentage of people from a Pakistani ethnic background, and the prevalence of long-term health problems, in a neighbourhood, were also associated with increases in IID admission rates. Conclusions: Increasing trends in neighbourhood deprivation, as measured by unemployment, were associated with increases in emergency IID admission rates for children and adults in England, despite controlling for measures of healthcare access, underlying morbidity and ethnicity. Research is needed to improve understanding of the mechanisms that explain these inequalities, so that effective policies can be developed to reduce the higher emergency IID admission rates experienced by more disadvantaged communities.